Prevalence and possible aetiological factors of molar incisor hypomineralisation in Saudi children: A cross-sectional study - Zahra Almuallem; Abdulmalik Alsuhaim; Abdulaziz Alqudayri; Sarah Aljarid; Mona Mousa Alotaibi; Rawan Alkraida; Rania Faden; Faten Mojaleed; Moatazbellah Alruwaithi; Haila Al-Huraishi (Elsevier, 2022)
Background: A new charting system for molar incisor hypomineralisation (MIH) was recently published and is based on the European Academy of Paediatric Dentistry (EAPD) criteria. This charting system aims to standardise MIH data collection. Therefore, there is a need for new MIH prevalence studies using the currently recommended charting-form. Aim: To investigate the prevalence and possible aetiological factors of MIH in randomly selected Saudi schoolchildren aged 8-12 years in Riyadh. Design: A randomly selected sample of Saudi schoolchildren aged 8-12 years attending elementary schools in Riyadh was examined using the EAPD short-form charting, which was recently recommended for the standardised collection of epidemiological data on MIH. To investigate possible aetiological factors of MIH, we collected demographic, pregnancy, and medical history using a questionnaire. Results: A total of 1,562 children participated in the study (48.8% girls, 51.2% boys). The prevalence of MIH was 15.2%, without a significant difference in the prevalence between the sexes. Among those with MIH, 79.4% had affected incisors and 55.9% had hypomineralised second primary molars. The most prevalent clinical defect was demarcated opacities, and the maxillary arch was more affected. Permanent incisors were more affected in boys than in girls. Defects of the first permanent molars were more severe in terms of clinical status and lesion extent than defects of the permanent incisors. MIH was significantly more prevalent in children with a history of early childhood ear infections, respiratory distress, and tonsillitis. Conclusions: MIH is common in Saudi schoolchildren living in Riyadh, with no gender predilection. Hypomineralised second primary molars can be used to predict MIH. MIH was significantly associated with childhood illness during the first three years of life, including ear infection, respiratory distress, and tonsillitis.